Penghapusan Merek Terdaftar yang Tidak Aktif dalam Perspektif Teori Kesejahteraan Menurut Jeremy Bentham - Masfufah Masfufah; Afifah Kusumadara; Yenny Eta Widyanti (Jurnal Ilmiah Kebijakan Hukum, 2024)
Trademarks play a vital role in modern trade, but in Indonesia, there is a normative conflict in Law No. 20 of 2016 concerning Trademarks and Geographical Indications between Article 74 Paragraph (1) and Article 35 Paragraph (1). How can a registered trademark be removed even though it is still within the protection period? The research method used is normative juridical with statutory, comparative, and case study approaches, utilizing primary, secondary, and tertiary legal materials that are analyzed descriptively. This research aims to analyze whether the provisions for the removal of registered trademarks in Indonesia uphold the principles of justice and legal certainty by emphasizing Jeremy Bentham’s welfare theory, in order to achieve appropriate regulations and harmonization between conflicting provisions. The results findings that the provision for removal registered trademarks are unfair and harmful to registered trademarks owners, as they disregard the principles of justice and legal certainty. Therefore, it is necessary to make a statement of the use of registered trademarks by the registered trademarks owner that is facilitated by the DJKI before the 10 year period so that there is harmonization between the conflicting provisions. The implementation of this solution is expected to provide legal certainty, encourage active use of trademarks, and support sustainable economic growth.